SOSIALISASI PERKEMBANGAN RUMAH ADAT NIAS: SEBUAH PERPADUAN SENI DAN BAHASA DALAM KEARIFAN LOKAL NIAS - Telaumbanu, Tatema (Haga : Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service activity aims to socialize the development of the Nias traditional house as an important element of local culture that unites the aspects of art, language, and traditional wisdom. The Nias traditional house, known as Omo Hada, is a symbol of cultural identity with historical, architectural, and spiritual values. This activity educates the community on the importance of preserving the Nias traditional house and its role in maintaining the diversity of local culture amidst the pressures of globalization. Through a participatory approach, this socialization involves the community in understanding the philosophy embedded in the structure and ornamentation of the traditional house, as well as how the local language plays a role in conveying cultural messages through each element of the house. Using methods such as lectures, discussions, and exhibitions, this activity aims to raise public awareness of the importance of maintaining and developing traditional houses as part of cultural heritage that must be passed on to future generations.